Perampanel Reduces Hyperthermia-Induced Seizures in Dravet Syndrome Mouse Model - Ho, Shih-Yin; Lin, Li; Chen, I-Chun; Tsai, Che-Wen; Chang, Fang-Chia; Liou, Horng-Huei (Frontiers in Pharmacology, 2021)
Treatment options for Dravet syndrome are limited. The aim of this study was to evaluate the antiepileptic effect of the AMPA receptor antagonist perampanel (PER) on a mouse model of Dravet syndrome (Scn1aE1099X/+). We report here that the PER (2 mg/kg) treatment inhibited the spontaneous recurrent seizures and attenuated epileptic activity in Scn1aE1099X/+ mice. In the hyperthermia-induced seizures experiment, PER clearly increased temperature tolerance and significantly ameliorated seizure frequency and discharge duration. The PER also demonstrated antiepileptic effects in a crossover study and a synergistic effect for attenuating heat-induced seizure when given in combination with stiripentol or valproic acid. The results showed that PER effectively decreased the occurrence of spontaneous recurrent seizures, and shows significant therapeutic potential for hyperthermia-induced seizures with regard to both susceptibility and severity in a Dravet syndrome mouse model. Potential therapeutic effects of PER for treatment of Dravet syndrome were demonstrated.